Предмет: Алгебра,
автор: Pularity1420
(6√6-√13)^2 + 12(√78+4)
помогите, ребятки
Ответы
Автор ответа:
3
(6√6 - √13)² +12(√78 +4) =
=(6√6)² -2*6√6 *√13 +(√13)² + 12√78 + 48 =
=36*6 -12√(6*13) +13 +12√78 +48 =
=216 - 12√78 +13 +12√78 +48 =
=216 +13 +48 =277
=(6√6)² -2*6√6 *√13 +(√13)² + 12√78 + 48 =
=36*6 -12√(6*13) +13 +12√78 +48 =
=216 - 12√78 +13 +12√78 +48 =
=216 +13 +48 =277
Pularity1420:
Благодарю :3
Похожие вопросы
Предмет: Окружающий мир,
автор: карина2183
Предмет: Русский язык,
автор: 1234567890987655
Предмет: Английский язык,
автор: Aleksuggg
Предмет: Биология,
автор: dashaborovsk2
Предмет: Математика,
автор: uwuowouwu